2015
DOI: 10.1002/da.22388
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Disorders Subsequent to Gestational Diabetes Mellitus Differ by Race/Ethnicity

Abstract: The incidence of mental health disorders subsequent to GDM was attenuated after adjustment for clinical and socioeconomic factors. Moreover, race/ethnicity influenced this relationship. Further investigation is warranted to clarify potential underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
31
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 41 publications
7
31
3
Order By: Relevance
“…Overall, 48 publications were included in this review (Figure 1, Table 1, Table 2, Table 3, Supplementary Table 1). Of these, 30 described prospective observational studies[20,21,23,24,26,27,29-31,34,35,37,38,41,43-45,47-49,51,54,57,58,60-62,65-67], 15 described retrospective observational studies[22,25,28,32,39,40,42,46,50,53,55,56,59,63,64], and three described randomized controlled trials (RCTs)[33,36,52], two of which reported only baseline data[36,52]. Two publications described the same study, but reported different subgroup analyses[23,29].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, 48 publications were included in this review (Figure 1, Table 1, Table 2, Table 3, Supplementary Table 1). Of these, 30 described prospective observational studies[20,21,23,24,26,27,29-31,34,35,37,38,41,43-45,47-49,51,54,57,58,60-62,65-67], 15 described retrospective observational studies[22,25,28,32,39,40,42,46,50,53,55,56,59,63,64], and three described randomized controlled trials (RCTs)[33,36,52], two of which reported only baseline data[36,52]. Two publications described the same study, but reported different subgroup analyses[23,29].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 28 studies included only women with GDM[20,23,26-29,31,33,35-38,40,43-45,47-49,51-53,57,58,60,61,63,64], 14 included women with either GDM or pre-existing diabetes (although the type was not always reported)[22,25,39,41,42,46,50,54-56,59,62,65,66], one included women with either GDM or type 1 diabetes[34], one included only women with type 1 diabetes[67], one included only women with pre-existing diabetes (type not reported)[30] and three did not report the type of diabetes[21,24,32] (Tables 1-3, Supplementary Table 1). Sample sizes ranged from 36[65] to more than 32 million in a retrospective analysis of a nationwide hospital database[22] (Tables 1-3, Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations